A comprehensive review on recent advances in fluorescence-based bio-analytes sensing - Mal, Dibya Kanti; Pal, Haridas; Chakraborty, Goutam (TrAC, Trends in analytical chemistry (Regular ed.), 2024)
Fluorescence-based sensing of bio-analytes is a hitherto emerging area in contemporary research, as the technique offers several advantageous features like non-invasiveness, high selectivity, high sensitivity, rapid responses in addition to its widespread applications in biologically important samples. Herein, we present a perspective on different underlying mechanisms, which play key roles in the luminescence-based sensing along with some recent progresses made across the globe in estimating bio-analytes like amino acids, ATP, protamine, sulfite, etc. This review comprises a comparative discussion on modulations in optical properties of different fluorescent probes by the presence of target analytes, highlighting their detection limits in analyte sensing. With the extensive coverage made in this article on fluorescence-based bio-analyte detections, covering mainly the various developments mostly after 2010, it is anticipated to make this review article quite unique and propitious to the impending academic and applied research in this subject domain on the years to come. [Display omitted] •This review discusses briefly about different fluorescence based sensing mechanism.•Gives a brief overview of different fluorescent probes used for various bio-analytes.•Provides a comparative evaluation of fluorescent probes used for a bio-analyte.•Inculcate the use of luminescence-based techniques for futuristic applications.